Transformasi Pembelajaran Sejarah Islam untuk Generasi Z melalui Konten Digital di Madrasah Aliyah Negeri (MAN) 4 Tungkop Aceh Besar - Muhammad, Imran (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2024)
This study aims to analyze the effectiveness of using digital content in the learning of Islamic history for Generation Z, who have grown up in the digital age. Generation Z has unique learning characteristics, preferring visual, interactive, and technology-based education. Therefore, this research examines how digital content such as animation videos, educational games, and social media influences students' interest and understanding of Islamic history. The method used is a survey with participants consisting of students from Islamic schools and secondary schools. The results show that the majority of students find Islamic history lessons more engaging and easier to understand when using digital content. Social media and YouTube are the primary platforms used, while animation videos and educational games are the most preferred types of content. The frequency of digital content use in learning is high, with most students using it several times a week. This study concludes that digital content can enhance the effectiveness of Islamic history education and provide a more engaging and relevant learning experience for Generation Z. Therefore, there is a need to integrate social media, animation videos, and infographics into the Islamic history curriculum to increase students' interest and understanding.